Fabrication and characterization of nanostructured ceramic thin films for electrochemical studies / Rabia Naeem - Rabia , Naeem (2017)
This work describes some general procedures for the synthesis and characterization of monometallic and heterobimetallic single source precursors [Cu2Ti4(O)2(OH)4(TFA)8(THF)6]∙THF (1), [Co2Ti4(μ-O)6(TFA)8(THF)6]·THF (2), [Mg2Ti4(O)2(OH)4(TFA)8(THF)6]∙THF (3), [Mn(dmae)2(TFA)4] (4) and [Sn(dmae)(OAc)]2 (5) and their disposal for the growth of thin films for electrochemical applications. The complexes have been characterized by m.p, elemental analyses, FT-IR, TG/DTG and single crystal X-ray analysis. The precursors (1), (2) and (3) were applied as a single source for the fabrication of CuO-2TiO2 and CoTiO3-TiO2 composites and MgTi2O5 solid solution thin films, whereas film precursor (4) has been applied as a dual source along with Ag(I) acetate for the deposition of Ag-Mn2O3 composite thin film by aerosol assisted chemical vapour deposition (AACVD). The electric field directed aerosol assisted chemical vapor deposition technique (EFDAACVD) was used to make thin films of SnO2, Mn2O3, Fe2O3, NiO, CuO, ZnO, CdO and PbO from precursor (5) and their respective acetates. Further CuPbI3 was synthesized by heating co-precipitated mixture of copper(I) iodide and lead(II) iodide in an evacuated Pyrex ampule at 630 oC. The films of CuPbI3 were decorated by electrophoretic deposition method. The phase purity, particle size and crystallinity of deposited thin films were examined by X-ray powder diffraction (XRPD) and Raman spectroscopy, while X-ray photoelectron spectroscopy (XPS), field emission scanning electron microscopy and energy dispersive X-ray spectroscopy (EDX) were used to investigate the oxidation states, electronic structure, surface morphology, shape and elemental composition of the involved elements. In the case of mesoporous nanostructure of SnO2 microballs surface area 136 m2g-1 was determined by BET. The optical band gaps of films were determined by UV-visible spectrophotometry and found to be were 1.8, 3.4, 3.8, 1.2, 2.2, 1.9,0.9,3.2, 2.2, 1.9 and 1.82 eV for Ag-Mn2O3, MgTi2O5, SnO2, Mn2O3, Fe2O3, NiO, CuO, ZnO, CdO, PbO and CuPbI3 films, respectively. The applicability of fabricated CuO-2TiO2 and CoTiO3–TiO2 composite electrodes in electrochemical sensors has been investigated towards the sensitive and selective detection of NO2− ions and dopamine (DA), respectively. The CuO-2TiO2 electrode showed the limit of detection (LoD) of 16.6 nM with the linear range of 10 to 200 μM at +1.0 V due to the oxidation of NO2− ions. The CoTiO3–TiO2 electrode showed good electrocatalytic activity for DA with the (LoD) of 0.083 μM and a linear range of 20 to 300 μM. The SnO2 micro balls provide unique network pores that could be easily penetrated by the electrolyte to give high reversible recycling stability for application in lithium ion batteries. The photoelectrochemical activity (PEC) of Ag-Mn2O3, MgTi2O5, Mn2O3, Fe2O3, NiO, CuO, ZnO, CdO, PbO and CuPbI3 thin films determined by the linear sweep voltammetry (LSV) show photocurrent densities of 3, 0.4, 1.2, 0.12, 0.23, 0.13, 0.23, 0.26, 0.20 and 0.25 mAcm-2 at 0.7 V vs Ag/AgCl/3M KCl, respectively. The improved photoelectrochemical behaviour of Ag-Mn2O3, MgTi2O5, Mn2O3, Fe2O3, NiO, CuO, ZnO, CdO, PbO and CuPbI3 electrodes was attributed to the increased photon absorption ability, increased surface area, and more efficient electron/hole transfer which were confirmed by LSV, Chronoamperometery, electrochemical impedance spectroscopy and Mott‐Schottky plot.